Penilaian Potensi Bahaya Dengan Metode Hira (Hazard Identification And Risk Assessment) Jalan Magelang - Purworejo: Hazard Potential Assessment Using the HIRA Method (Hazard Identification and Risk Assessment) Magelang - Purworejo Road - Octavioliena, Zahwa; Hadi, Suprapto (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Road safety is a crucial aspect that must be prioritized when planning a transportation system. In 2023, Magelang Regency recorded 1,016 accident cases, resulting in 154 fatalities. One of the contributing factors to these accidents is road conditions. The Magelang-Purworejo Provincial Road faces significant challenges, particularly due to its steep and lengthy descents, which are a major cause of accidents. Drivers, especially those operating heavy-loaded vehicles, often struggle to control their speed on sharp declines, especially during slippery or rainy conditions. This study aims to identify potential hazards on the Magelang-Purworejo Provincial Road to reduce the risk of accidents and fatalities caused by road hazards. Using the Hazard Identification Risk Assessment (HIRA) method, the safety inspection analysis for the Magelang-Purworejo Road—a primary collector road with a provincial status and a 2/2 UD type—revealed several key hazards, including uneven shoulder height, road damage, obstructed traffic signs, and limited visibility. Based on the risk assessment, 18% of hazards are categorized as low level, 76% as moderate, and 6% as high, with major consequences accounting for 24%, and the highest likelihood of accidents reaching 41%. Improvement recommendations have been proposed to mitigate these risks and enhance the safety of road users.